Evaluate of Coffee Husk Compost - Endar Hidayat; Asmak Afriliana; Gusmini Gusmini; Masuda Taizo; Hiroyuki Harada (International Journal on Food, Agriculture and Natural Resources, 2020)
Purpose In this study, to evaluate the physico-chemical properties of coffee husk compost. Methods The compost process in aerobic condition for 84 days. Physico-chemical parameters were analyzed. In addition, the seed germination, leaf width, stem length and fresh weigh yield of compost were investigated on matured compost using Brassica rapa. Results The obtained results indicate that the pH value 7.72 and EC value 12.54 ms/cm. The total carbon value 37.41%. The total nitrogen value 2.05%. The C/N ratio value 18.2. The seed germination indicate that compost was matured with range 80-100%. On compost yields the optimum doses of the Brassica rapa 3% with leaf width 1.3 cm, stem length 5.1 cm and fresh weight 2.18 gram. Conclusion Generally, the final compost can be served as organic matter for improving soil and plant.